An investigation of L. monocytogenes in the South African ready-to-eat prepared-fruit industry - Esterhuysen, Michael Keaton (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.